2019
DOI: 10.1111/1752-1688.12766
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Adaptation to Drought for Different Cropping Systems in Southern China under Climate Change

Abstract: This study investigates agricultural adaptation to drought for different cropping systems in southern China. The study area was divided into three regions: South China (SC), South of the Yangtze River (SYR), and Southwest China (SWC). An index of agricultural adaptation to drought (D) was established. Our findings indicated that the average total crop water demand varied greatly among the regions from 1961 to 2010 in southern China. The maximum value was found in the SC region, followed by the SYR and SWC regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Guangxi is located in the south of China and belongs to the subtropical humid monsoon climate zone, where rocky hills are widely distributed, and karsts are developed, leading to the coexistence and alternation of drought and flood disasters; among them, flash droughts and seasonal droughts are frequent and coexist (Wang and Yuan, 2021). In addition, Guangxi is a large agricultural province, crops are mostly planted on sloping land and mainly rain‐fed, and crop growth in the region is extremely sensitive to the response of meteorological drought (Zhao et al ., 2019; Zhang et al ., 2020a). In recent years, international research on drought events, on the one hand, is gradually changing from the traditional monthly and above time scales and single‐factor feature statistics to more refined time scales and comprehensive measures of multiple factors (Wang et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Guangxi is located in the south of China and belongs to the subtropical humid monsoon climate zone, where rocky hills are widely distributed, and karsts are developed, leading to the coexistence and alternation of drought and flood disasters; among them, flash droughts and seasonal droughts are frequent and coexist (Wang and Yuan, 2021). In addition, Guangxi is a large agricultural province, crops are mostly planted on sloping land and mainly rain‐fed, and crop growth in the region is extremely sensitive to the response of meteorological drought (Zhao et al ., 2019; Zhang et al ., 2020a). In recent years, international research on drought events, on the one hand, is gradually changing from the traditional monthly and above time scales and single‐factor feature statistics to more refined time scales and comprehensive measures of multiple factors (Wang et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These changes may have adverse impacts on future water distribution patterns in the area, and thus agricultural production (Georgakakos et al ., 2014; Sterle et al ., 2020). Several studies have reported a close relationship between climate changes and increased losses in rice and wheat yields due to higher temperatures and unfavourable rainfall patterns (Mohammed and Tarpley, 2009; Ran et al ., 2018; Qu et al ., 2019; Yang et al ., 2019; Zhao et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The scientific community is also focused on climate change adaptation issues because of the increased understanding that inertia in the climate system will necessitate adaptation in the long term [2]. Crops in China will likely be strongly affected by meteorological disasters unless states and communities can quickly adapt their agricultural practices [3,4].…”
Section: Introductionmentioning
confidence: 99%